Politics and Pluralism: Analyzing State Official Tafsir and Interfaith Discourse in Indonesia - Achmad Yafik Mursyid; Muhammad Dzilfikri AlBaihaqi; Alvy Ra'isatul Murtafi'ah (UIN Sunan Kalijaga Yogyakarta, 2024)
This research aims to explore the Tafsir produced by the Ministry of Religious Affairs of the Republic of Indonesia, specifically focusing on the potential politicization of the Qur’an, particularly in the narrative of inter-religious relationships in Indonesia. The study underscores the crucial role of Tafsir in shaping societal perceptions of religious pluralism in the country. In this context, a significant question arises concerning the extent to which the interpretations generated through the state's political mechanisms contribute to the discourse on religious pluralism. To address this inquiry, the critical discourse analysis approach by Norman Fairclough is employed, encompassing three dimensions: text analysis, discursive practices, and social practices. The analysis focuses on the Tafsir produced in 1980 by the Indonesian Ministry of Religious Affairs titled